MYCORRHIZAL FUNGI INCREASED EARLY GROWTH OF TROPICAL TREE SEEDLINGS IN ADVERSE SOIL - Maman Turjaman; Erdy Santoso; Irnayuli R. Sitepu; Keitaro Tawaraya; Erry Purnomo; Ronny Tambunan; Mitsuru Osaki (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2009)
The rate of reforestation has increased throughout the countries in Southeast Asia region during the last 20 years. At the same time, inconvenient situations such as forest destruction, forest exploitation, illegal logging, clear-cut forest areas, old agricultural lands, post-wildfire areas, conversion of natural forests into plantations, resettlement areas, mine lands, and amended adverse soils have also been increasing significantly. Mycorrhizas, hovewer, play important role to increase plant growth, enrich nutrient content and enhance survival rates of forest tree species in temperate and sub-tropical regions. Unfortunately, a little information so far is available regarding the effect of mycorrhizas on growth of tree species growing in tropical forests. In relevant, several experiments were carried out to determine whether ectomycorrhizal (ECM) fungi and arbuscular mycorrhizal (AM) fungi can enhance mycorrhizal colonization, nutrient content, and plant growth of some tropical rain forest tree species in Indonesia under nursery and field conditions. The families of tropical tree species used in the experiment were Thymelaeaceae (Aquilaria crassna), Leguminosae (Sesbania grandifolia), Guttiferae (Ploiarium alternifolium and Calophyllum hosei), Apocynaceae (Dyera polyphylla and Alstonia scholaris), and Dipterocarpaceae (Shorea belangeran). These families are important as they provide timber and non-timber forest products (NTFPs). This paper discusses the role of mycorrhizal fungi in increasing early growth of tropical tree seedlings in adverse soil.